IgA nephropathy in a child: Crohn's disease-associated or adalimumab induced?. (2nd January 2022) - Graziano, Francesco; Busè, Martina; Cassata, Nicola; Lentini, Vincenzo Luca; Citrano, Michele
Abstract: In pediatric patients with Inflammatory Bowel Disease renal parenchymal disease is infrequent. There are only two reports about the association between IgA Nephropathy and Pediatric Crohn Disease. IgA Nephropathy is a rather uncommon complication of Tumor Necrosis Factor-alpha (TNF-α) inhibition. We describe a case of IgA Nephropathy which has arisen in a 11-year-old child 2 years after Crohn disease diagnosis, during therapy with anti–TNF-α. An ileal e jejunal Crohn disease was diagnosed at 9 years old, initially treated with prednisone, followed by biological therapy with anti-TNF-α (Adalimumab) due to severe disease activity, with gradual improvement of clinical conditions until clinical remission is achieved. Two years after the diagnosis, the child suddenly presented macroscopic hematuria. Subsequent laboratory examinations showed acute renal failure. So kidney biopsy was performed and IgA Nephropathy diagnosis was made. Adalimumab was discontinued and the child has been treated with steroids for sixth months associated with angiotensin-converting enzyme inhibitor resulted in clinical improvement over the following year and remission was maintained. To our knowledge the association of IgA Nephropathy and pediatric IBD during therapy with anti-TNF-α has never been reported. Careful monitoring of renal function, proteinuria, and autoantibodies is advised in patients treated with anti-TNF-α agents.